Motivations for Studying Abroad and Immigration Intentions: The Case of Vietnamese Students - Nghia, Tran Le Huu (Journal of International Students, 2019)
This article reports a study that investigated prospective and current Vietnamese international students’ motivations to study abroad and their immigration intentions. Analyses of 55 intercept interviews and 313 responses to a survey revealed 12 push and pull factors that motivated students to pursue overseas studies and 18 sociocultural, economic, and political factors that influenced their immigration intentions. Independent samples t tests indicated that there were statistically significant differences in the influence of motivations on decisions to study overseas between groups of male and female students and prospective and current students. The analyses, furthermore, suggested that students’ immigration intentions depended on their personal attachment to the home country and (perceived) adaptability to the host country.